Understanding the success motivators in scholarly publishing: A case of high ranked Malaysian scientists - Mohd Napiah, Mohd Kamal; Abdullah, Abrizah; Gurmit Singh, Kiran Kaur (Malaysian Journal of Library and Information Science, 2022)
Research is the cornerstone of the development of a nation, and its researchers play pivotal roles for social and economic progress of the country. Among those researchers, there are groups of successful scientists with outstanding accomplishment in research; who are experts in their field, productive in delivering quality papers, highly cited by peer researchers and receive prestigious recognition locally and globally. This study aims to identify the motivation that influences top Malaysian scientists to be successful in scholarly publishing. The data presented comes from interviews with nine high ranked Malaysian scientists with an attempt to demonstrate that scientists’ success in scholarly publishing is derived from four motivational needs, namely achievement, affiliation, authority and avidity, represented by quotes or comments. The findings show that high ranked scientists were motivated mainly by inclination towards affiliation and achievement, as compared to authority and avidity. Overall, findings from this study have provided useful information on the characteristics and motivation of high ranked scientists that may be of value as reference indicators for future top scientists in the country.